The perceptual - Cognitive skills of combat sports athletes: A systematic review - Russo, G.; Ottoboni, G. (Psychology of Sport and Exercise, 2019)
The aim of this review is to provide evidence of how practicing combat sports can shape the perceptual - cognitive skills of athletes. This is because they must be adept at selecting the relevant stimuli in order to anticipate the attack and decide how counterattack their opponent in order to achieve victory. A systematic search was conducted on PsycINFO, Scopus and Web of Science via the combination of specific keywords. 31 research articles were included. Different aspects of perceptual-cognitive skills were analysed, such as complex cognitive skills and basic cognitive functions. The investigations were divided by the methods and stimuli used. The results are reported in three chapters: one analysed the research conducted with realistic stimuli (videos/pictures), another chapter investigated the studies with simulated scenarios, while the last chapter examined the basic cognitive functions. Following this is a chapter which, instead, analysed an important aspect for future studies: perceptual-cognitive training. The studies revealed better general anticipation skills with real and simulated stimuli, and better cognitive functions with regards to attention for experts than novices. However, a comprehensive analysis is needed to understand the results which emerged from the investigation. Moreover, the review aims to encourage possible future research in the topic area.